2019
DOI: 10.1177/0300060519892432
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment curcumin reduced ischemia–reperfusion-induced pulmonary injury via the Notch2/Hes-1 pathway

Abstract: Objective To investigate the influence of curcumin on the Notch2/Hes-1 pathway after pulmonary injury induction via limb ischemia–reperfusion (I/R). Methods Adult male Sprague–Dawley rats were randomly divided into four groups (n = 30 each): sham, I/R, curcumin post-treatment (I/R+Cur), and inhibitor (I/R+DAPT). Hind-limb ischemia was induced for 4 hours, followed by reperfusion for 4 hours. After ischemia, curcumin (200 mg/kg) or DAPT (0.5 µm) was injected intraperitoneally in the I/R+Cur or I/R+DAPT group, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Furthermore, limb I/R could induce the activation of neutrophils, monocytes and macrophages, which can promote inflammation and release a large number of inflammatory mediators, including cytokines and chemokines ( 21 ). Inflammatory factors in the ischemic area and the extensive release of oxygen free radicals cause damage to distal organs and the lung is particularly susceptible to acute injury ( 22 ). Previous studies on animal models have demonstrated that the expression levels of inflammatory cytokines, such as TNF-α, IL-1, IL-6 and IL-8, are significantly increased after limb I/R ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, limb I/R could induce the activation of neutrophils, monocytes and macrophages, which can promote inflammation and release a large number of inflammatory mediators, including cytokines and chemokines ( 21 ). Inflammatory factors in the ischemic area and the extensive release of oxygen free radicals cause damage to distal organs and the lung is particularly susceptible to acute injury ( 22 ). Previous studies on animal models have demonstrated that the expression levels of inflammatory cytokines, such as TNF-α, IL-1, IL-6 and IL-8, are significantly increased after limb I/R ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Previous studies have confirmed that ischaemia-reperfusion of the limbs in rats can activate the Notch2/ Hes-1 signalling pathway, which ultimately leads to renal injury. 4,5 The use of curcumin post-condition can inhibit the toll-like receptor 4 (TLR4)/nuclear transcription factor jB (NF-jB) signalling pathway to reduce the lung injury induced by limbs ischaemiareperfusion. 6 MicroRNA (miR-21) is a popular research topic in the field of cell apoptosis and it inhibits cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bo and Feng supported the fact that the oral route of administration requires more time between the administration and the ischemia-reperfusion event. 57 …”
Section: Discussionmentioning
confidence: 99%